2019
DOI: 10.1002/cssc.201900928
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Diphenylamines from Phenols and Ammonium Formate Catalyzed by Palladium

Abstract: Arylamines are commerciallya nd synthetically useful compounds with aw ide variety of applications.T heir preparation has been traditionally achieved using metal-catalyzedC ÀN coupling reactions with aryl halides. In this work, 17 different diarylamines are prepared from phenolsb yu sing ammonium formate as the aminatingr eagent. Phenolicc ompounds are more desirable feedstocks, owing to their availability from lignin, making them valuable biorenewable alternatives to aryl halides. Ammonium formate is found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Similar to N-cyclohexyl aniline, diphenylamine was accessible from the reductive amination of lignin-derived phenolic model monomers as delineated in Scheme 13. The first and unique example for the synthesis of diphenylamine from reductive amination of phenol was done by Li et al [155] using Pd/C and ammonium formate as catalyst and nitrogen/hydrogen sources, respectively. Up to 98% yield of diphenylamine was achieved under argon atmosphere at 160 °C in 24 h. Moreover, the authors reported 17 different diarylamines synthesized from the reductive amination of phenols with moderate to excellent yields (25-98%) using the described catalytic system [155].…”
Section: Phenolic Lignin Model Monomers + Hcoonhmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to N-cyclohexyl aniline, diphenylamine was accessible from the reductive amination of lignin-derived phenolic model monomers as delineated in Scheme 13. The first and unique example for the synthesis of diphenylamine from reductive amination of phenol was done by Li et al [155] using Pd/C and ammonium formate as catalyst and nitrogen/hydrogen sources, respectively. Up to 98% yield of diphenylamine was achieved under argon atmosphere at 160 °C in 24 h. Moreover, the authors reported 17 different diarylamines synthesized from the reductive amination of phenols with moderate to excellent yields (25-98%) using the described catalytic system [155].…”
Section: Phenolic Lignin Model Monomers + Hcoonhmentioning
confidence: 99%
“…The first and unique example for the synthesis of diphenylamine from reductive amination of phenol was done by Li et al [155] using Pd/C and ammonium formate as catalyst and nitrogen/hydrogen sources, respectively. Up to 98% yield of diphenylamine was achieved under argon atmosphere at 160 °C in 24 h. Moreover, the authors reported 17 different diarylamines synthesized from the reductive amination of phenols with moderate to excellent yields (25-98%) using the described catalytic system [155]. Furthermore, the authors clearly elaborated the possible reaction mechanism taking the reductive amination of phenol with ammonium formate as an example [155].…”
Section: Phenolic Lignin Model Monomers + Hcoonhmentioning
confidence: 99%
“…In 2019 a similar protocol was reported by Li and co-authors. [359] They used cyclohexenone to insert the third phenyl ring in the Ph 2 NH structure in the presence of Pd on carbon (Scheme 139). Scheme 139.…”
Section: Metal-free Reactions Of Amines and Aryl Halidesmentioning
confidence: 99%
“…In 2019, our group used the same strategy to directly synthesize diarylamines from phenols and ammonium formate (Scheme 5). 15 Various diarylamine products were obtained in good to excellent yields except for severely sterically hindered substrates bearing multiple ortho substituents. Although large amounts of phenols are required to increase the yield, the phenols could be recovered after the reaction.…”
Section: Synpacts Synlettmentioning
confidence: 99%